2019
DOI: 10.1001/jamapsychiatry.2019.2508
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Liability to Psychotic Experiences With Neuropsychotic Disorders and Traits

Abstract: IMPORTANCE Psychotic experiences, such as hallucinations and delusions, are reported by approximately 5% to 10% of the general population, although only a small proportion develop psychotic disorders such as schizophrenia. Studying the genetic causes of psychotic experiences in the general population, and its association with the genetic causes of other disorders, may increase the understanding of their pathologic significance. OBJECTIVES To determine whether genetic liability to psychotic experiences is share… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
124
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 59 publications
(112 reference statements)
6
124
2
1
Order By: Relevance
“…We did not find any significant association between PRSSZ and total number of PLEs in the entire UKBiobank sample (N = 308,693), consistent with previous studies investigating this relationship in adolescence [65,66]. A recent UKBiobank study found a weak association between the presence of any PLEs and PRSSZ at a threshold of P ≤ 0.05 (OR, 1.09; 95% CI, 1.06-1.12; adjusted R2 = 0.001; P = 2.96x10 −11 , N = 500,000); however, as the authors noted, this association may be biased by the possibility that their analysis included sample overlap between UKBiobank and the training sets [9].…”
Section: Psychotic-like Experiencesmentioning
confidence: 92%
See 1 more Smart Citation
“…We did not find any significant association between PRSSZ and total number of PLEs in the entire UKBiobank sample (N = 308,693), consistent with previous studies investigating this relationship in adolescence [65,66]. A recent UKBiobank study found a weak association between the presence of any PLEs and PRSSZ at a threshold of P ≤ 0.05 (OR, 1.09; 95% CI, 1.06-1.12; adjusted R2 = 0.001; P = 2.96x10 −11 , N = 500,000); however, as the authors noted, this association may be biased by the possibility that their analysis included sample overlap between UKBiobank and the training sets [9].…”
Section: Psychotic-like Experiencesmentioning
confidence: 92%
“…Psychotic-like experiences (PLEs) of lesser severity are present not only in patients but also in 5-8% of the general population [5], and to some extent predict transition to psychiatric disorders among those with higher PLEs [6]; with cohort studies supporting a continuity between subclinical and clinically significant psychotic symptoms [7,8]. A recent study found shared genetic aetiology between PLEs and several psychiatric and neurodevelopmental disorders, indicating that PLEs may be related to a general risk for mental health disorders [9]. Studies of the relationship between PLEs and brain imaging metrics have, however, been scarce and characterised by small sample sizes (with N ranging from 25 for auditory hallucinations to 76 for any PLEs [10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…One well-powered molecular genetic analysis has recently detected shared genetic covariance of psychotic experiences (e.g., auditory/visual hallucinations and delusions) with schizophrenia and with four other psychiatric disorders using interview data from UK Biobank. 4 These results are promising for genetic studies of subthreshold psychosis symptoms, since schizotypy measures provide increased variation and sensitivity with respect to risk-a key empirical finding from the literature on subthreshold negative symptoms. [11][12][13] The availability of symptom and common variant genetic data in a large population-based cohort, the Generation Scotland Scottish Family Health Study (N = 9,105 individuals aged 18-65 years), yields the unique opportunity to examine associations of these symptoms with polygenic risk for schizophrenia.…”
Section: Introductionmentioning
confidence: 91%
“…Because of potential for clinically significant overlap of items with other psychiatric symptoms, we followed up with additional analyses of polygenic risk for the four other psychiatric disorders examined in analyses of UK Biobank-major depression, bipolar disorder, autism spectrum disorder, and ADHD. 4 Recent data from the World Health Organization have suggested that psychotic experiences may be much less specific to schizophrenia than previously thought. 1 Indeed, psychotic experiences appear to lie on the continuum of neuroticism, and have been observed to either precede or follow the onset of a range of non-psychotic psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) indicate modest single-nucleotide polymorphism heritability (SNP-h 2 ) for some PENS in mid-adolescence (3%-9%) and for schizotypy in adults (20%-27%) [20][21][22] . Psychotic experiences share genome-wide genetic influences with schizophrenia and major depression 20,[23][24][25][26] , although not all studies found this, particularly those that used comparatively smaller samples or polygenic scores (PGS) from less well-powered GWAS 23,24,[27][28][29][30][31] . Schizophrenia PGS has been associated with schizotypy in adults assessed using semi-structured interviews, but not with self-rated PENS 32 .…”
Section: Introductionmentioning
confidence: 99%